1 and 2 Thessalonians through the Centuries. By Anthony C. Thiselton - Luz, Ulrich (The journal of theological studies, 2013)
When a scholar like Anthony C. Thiselton, one of the world’s leading experts of hermeneutics, publishes a commentary whose focus is on reception history it raises great expectations. Thiselton’s model of reception history follows closely Hans Robert Jauss: he asks what is the ‘horizon of expectation’ of readers in a certain epoch and if their reading is an experience of surprise, innovation, or alienation that transformed their given horizon of expectation. Thiselton’s special concern is what Jauss calls ‘provocation’ by the text. This is when the tension between the horizon of expectation of readers and the texts in a given period of the history of interpretation ‘is sharp it may challenge the reader to rethink his or her expectations’ (p. 4).